Population Genetics - Trindade Maia, Rafael; Campos de Araújo, Magnólia (IntechOpen, 2022)
Population genetics is a theoretical field of biology that studies allelic and genetic frequencies in living organisms, thus allowing us to infer what evolutionary processes are acting on individuals over generations and predict the adaptive consequences of these changes in the gene pool. Knowing the structure and genetic diversity of populations is essential for a proper understanding of the evolution, speciation processes, and dynamics of living beings. This knowledge is extremely useful for some practical applications, such as species management and conservation strategies, vector and pathogen monitoring and control, plant and animal breeding, and genetic improvement. This book includes carefully selected works in population genetics reviewed by geneticists.